Vacuum structure of vector mesons in QCD - Rennecke, Fabian (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We study the chiral dynamics of vector mesons in two-flavor QCD in vacuum by utilizing a functional renormalization group approach. This allows us to capture the dynamical transition from the quark-gluon phase at high energies to the hadronic phase at low energies without the necessity of model parameter tuning. We use this to analyze the scaling of vector meson masses towards the chiral symmetry breaking scale, the decoupling of the mesons at high energies, and the validity of vector meson dominance.
Gesehen am 18.06.2020